Seed-borne pathogenic fungi on some soybean varieties - Loekas Soesanto; Annisa Rahmaddila Rizky Hartono; Endang Mugiastuti; Heri Widarta (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Soesanto L, Hartono ARR, Mugiastuti E, Widarta H. 2020. Seed-borne pathogenic fungi on some soybean varieties. Biodiversitas 21: 4010-4015. The present study was conducted to detect and identify seed-borne pathogenic fungi in some soybean varieties and their effect on seed germination. Experiment was performed in a completely random design with eight treatments and four replicates. Eight soybean varieties i.e., Malabar, Kaba, Dering, Detam I, Sinabung, Dena, Gepak Kuning, and Slamet were selected for the investigation. Seed borne fungi were isolated using blotter test and agar plate techniques. The variables observed were morphological/cultural characteristics, microscopic features of fungi, and percentage of seed germination. A total of eight fungi namely Aspergillus flavus Link, Aspergillus niger van Tieghem, Cladosporium oxysporum Berk. & M.A. Curtis, Colletotrichum dematium (Pers. et Fr.) Grove f.sp. truncate (Schw.) Arx, Curvularia pallescens Boedijn, Fusarium solani (Mart.) Sacc., Melanospora zamiae Corda, and Nigrospora sp. Mason were isolated from different varieties of soybean seeds. The highest seed germination was found to be 80.5% in Daring and Detam I varieties, respectively, and the lowest 53% was recorded in Dena variety.